STUDI AGLOMERASI KEGIATAN EKONOMI (STUDI KASUS DI LOMBOK EPICENTRUM MALL MATARAM) - DINDA RAHMI UTARI; PUTU KARISMAWAN; EMI SALMAH (GANEC SWARA, 2020)
Lombok Epicentrum Mall as one of business centre in Mataram city due to great performance building, many accessibilities that create spatial concentrations of economic activities.  The traders  chose the location in the Lombok Epicentrum Mall because of the benefits of agglomeration obtained in terms of the number of visitors, accessibility and lead to the increase of income. Paired Sample t test analysis show there were  significant differences income of traders between before and after doing business in Lombok Epicentrum Mall